Simple formulas for the calculation of the average physical optics RCS of a cylinder and a flat plate over a symmetric window around broadside. - Hestilow, Travis J.
Closed-form formulas for the arithmetic-average radar cross section (RCS) of a perfectly conducting cylinder and of a perfectly conducting rectangular plate are derived. The derivations proceed under the assumption that the conditions governing the use of the physical optics approximation are satisfied. Examination of the behavior of these formulas reveals simple approximations of very reasonable accuracy. The approximations allow quick and easy evaluation of dynamically collected RCS data in which the scattering phenomenology can be modeled by either a cylinder or a rectangular plate.
Keywords: Approximation methods; Electromagnetic scattering; Mathematics; Physical optics; Radar cross sections; Radar scattering; Statistics